Let K be a positive integer and X > 1
I f ∑ N = 1 ∞ X N N K = ( X − 1 ) K + 1 ∑ J = 0 K − 1 b K − J ∗ X K − J
where b 1 = b K = 1 and each constant b i where ( 2 < = i < = K − 1 ) is a positive integer
t h e n
∑ N = 1 ∞ X N N K + 1 = ( X − 1 ) K + 2 X K + 1 + ( ∑ J = 0 K − 2 ( ( K − J ) ∗ b K − J + ( J + 2 ) ∗ b K − J − 1 ) ∗ X K − J ) + X
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
What are b1, b2 , b3, ... , bk? Are they constants? How do we determine these values?
Log in to reply
Each constant b i where ( 2 < = i < = K − 1 ) is a positive integer and b 1 = b K = 1 .
Given ∑ N = 1 ∞ X N N K = ( X − 1 ) K + 1 ∑ J = 0 K − 1 b K − J ∗ X K − J , you want to obtain the next summation ∑ N = 1 ∞ X N N K + 1 in terms of these constants.
For instance, if you derived
∑
N
=
1
∞
X
N
N
3
=
(
X
−
1
)
4
X
3
+
4
X
2
+
X
,
then using the next summation above we obtain:
∑
N
=
1
∞
X
N
N
4
=
(
X
−
1
)
5
X
4
+
1
1
X
3
+
1
1
X
2
+
X
.
Starting with ∑ N = 1 ∞ X N N = ( X − 1 ) 2 X we can obtain each next summation using the above.
Problem Loading...
Note Loading...
Set Loading...
Let K be a positive integer.
Replace X by X 1 in ∑ N = 1 ∞ X N N K = ( X − 1 ) K + 1 ∑ J = 0 K − 1 b K − J ∗ X K − J ⟹
∑ N = 1 ∞ N K ∗ X N = ( 1 − X ) K + 1 ∑ J = 0 K − 1 b K − J ∗ X J + 1
d / d x ( ∑ N = 1 ∞ N K ∗ X N ) = ( 1 − X ) K + 2 ∑ J = 0 K − 1 ( J + 1 ) ∗ b K − J ∗ X J − ∑ J = 0 K − 1 ( J + 1 ) ∗ b K − J ∗ X J + 1 + ( K + 1 ) ∗ ∑ J = 0 K − 1 b K − J ∗ X J + 1 =
[ b K + ( K ∗ b K + 2 ∗ b K − 1 ) ∗ X + ( ( K − 1 ) ∗ b K − 1 + 3 ∗ b K − 2 ) ∗ X 2 + . . . +
( ( K − J ) ∗ b K − J + ( J + 2 ) ∗ b K − J − 1 ) ∗ X J + 1 + . . . + ( 2 ∗ b 2 + K ∗ b 1 ) ∗ X K − 1 + b 1 ∗ X K ] / ( 1 − X ) K + 2 = ( 1 − X ) K + 2 b K + ( ∑ J = 0 K − 2 ( ( K − J ) ∗ b K − J + ( J + 2 ) ∗ b K − j − 1 ) ∗ X J + 1 ) + b 1 ∗ X K ⟹
∑ N = 1 ∞ N K + 1 ∗ X N = ( 1 − X ) K + 2 b K ∗ X + ( ∑ J = 0 K − 2 ( ( K − J ) ∗ b K − J + ( J + 2 ) ∗ b K − j − 1 ) ∗ X J + 2 ) + b 1 ∗ X K + 1
Replacing X by X 1 ⟹
∑ N = 1 ∞ X N N K + 1 = ( X − 1 ) K + 2 X K + 1 + ( ∑ J = 0 K − 2 ( ( K − J ) ∗ b K − J + ( J + 2 ) ∗ b K − J − 1 ) ∗ X K − J ) + X